Determinants of Immunization Among Children Aged 12-23 Months in Ethiopia: A Proportional Odds Model Approach - Tefera, Mesay; Sharma, M.K. (International Journal of Statistics in Medical Research, 2015)
Childhood immunization is recognized as one of the most cost-effective public health interventions to prevent morbidity and mortality caused by infectious diseases, particularly in a high-endemic setting. According to the 2011 EDHS report by the Central Statistical Agency (CSA) of Ethiopia, nationally, only 24 percent of children age 12-23 months was fully immunized at the time of the survey. The main objective of this study was to identify and describe the determinants of immunization among children aged 12-23 months in Ethiopia. The source of the data was the Ethiopian Demographic and Health Survey conducted in 2011 (EDHS) 2011. In order to meet our objectives descriptive, and ordinal logistic regression (proportional odds model) statistical techniques were used for data analysis using socio-economic and demographic variables as explanatory variables and immunization status of children aged 12-23 months as the response variable. The results of the analysis predicts that place of delivery, wealth index, possession of radio and region were found to be significant determinants for full immunization among children aged 12-23 months in Ethiopia.